Preparation method of polymer filler containing silk fibroin particles
By preparing polymer fillers containing silk fibroin particles, combined with thiolated hyaluronic acid and thiol collagen fibers, hydrogen peroxide cross-linking technology is used to solve the problem of the thermodynamic instability and degradation speed of polymer fillers, the optimization of the thermodynamic stability and biodegradation performance of the material is achieved, the degradation time is extended, and the better tissue regeneration scaffold is provided.
Patent Information
- Application Number
- CN202510053643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-14
AI Technical Summary
In the prior art, polymer fillers have problems of thermodynamic instability and degradation speed in the application of biomedical fields, which are difficult to meet the needs of tissue regeneration and support.
By preparing polymer fillers containing silk fibroin particles, combining thiolated hyaluronic acid and thiolated collagen fibers, hydrogen peroxide cross-linking technology is used to form materials with improved mechanical properties and prolong degradation time.
The thermodynamic stability and biodegradation performance of the material are optimized, the degradation time is extended, and the tissue regeneration scaffold is provided, which has the advantages of a variety of materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer fillers, in particular to a method for preparing a polymer filler containing silk fibroin particles. Background Art
[0003] Silk fibroin is a natural and ancient protein material that can be extracted from artificially cultivated silkworm cocoons. It has good biocompatibility, adjustable biodegradability, and non-immunogenicity. It can be used as a suture material in the biomedical field and is a biomaterial that can be used clinically. Silk fibroin materials are easy to process, but they are thermodynamically unstable. They can be regulated by physical and chemical methods to increase the content of β-folded structures in silk fibroin and gradually transform them into thermodynamically stable structures. This structural controllability and rapid transformation ability allow silk fibroin materials to be used as tissue engineering materials. The material's morphology, mechanical properties, biodegradability, etc. can be flexibly regulated according to actual needs.
[0004] On the other hand, silk fibroin is rich in 18 kinds of amino acids. It is not only non-toxic to the tissue body, but its degradation products will not cause adverse reactions. At the same time, there are already many dressing products containing silk fibroin on the market, which proves the biosafety of silk fibroin. Therefore, silk fibroin can be used as a raw material for implant filling. Different tissue parts have different requirements for the size of filling particles. Silk fibroin has good morphological processability, which allows silk fibroin particles to be compounded with other polymers such as collagen and hyaluronic acid.
[0005] In order to solve the above problems, the present invention provides a method for preparing a polymer filler containing silk fibroin particles. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a polymer filler containing silk fibroin particles to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a polymer filler containing silk fibroin particles comprises the following steps:
[0009] Step 1: taking the degummed silk, dissolving it with a lithium bromide solution to obtain dissolved silk fibroin; cooling, dialyzing, and taking out the dissolved silk fibroin to obtain a silk fibroin solution;
[0010] Step 2: taking the silk fibroin solution, filtering, centrifuging, concentrating at 60-65° C., and adding injection water to dilute to obtain a diluted silk fibroin solution;
[0011] Step 3: placing the diluted silk solution at 60-65°C until a silk gel is formed;
[0012] Step 4: Take the silk fibroin gel, granulate it, add the concentrated silk fibroin solution to the granulated silk fibroin gel particles, mix them evenly, freeze them at -40°C to -80°C for 24-48h, freeze-dry them, place them at 25-30°C to absorb moisture for 1-3d, and crush them to obtain freeze-dried silk fibroin particles;
[0013] Step 5: Mix the lyophilized silk fibroin particles, thiolated hyaluronic acid, and deionized water evenly, use sodium hydroxide solution to adjust the pH value of the system to 8-8.5, add thiolated sheep collagen fiber particles, mix evenly at 0-2°C, add hydrogen peroxide, react at 35-40°C for 20-30 minutes, dialyze, and freeze-dry to obtain particles A; take particles A and sodium hyaluronate gel, mix evenly to obtain a polymer filler containing silk fibroin particles.
[0014] More optimally, in step 1, the bath ratio of the degummed silk to lithium bromide is 1:(4-10).
[0015] More optimally, in step 2, the concentration of the diluted silk fibroin solution is 2wt%-6wt%.
[0016] More optimally, in step 4, the mass ratio of the silk fibroin gel particles after granulation to the silk fibroin in the concentrated silk fibroin solution is 1:(0.2-2).
[0017] More optimally, in step 2, the centrifugation condition is: centrifugation at 9000 rpm for 20-30 min.
[0018] More optimally, the preparation method of the thiolated sheep collagen fiber particles is: mix the sheep collagen fibers and acetic acid evenly to obtain a sheep collagen fiber solution, cool it to 2-3°C, add N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, mix evenly, react for 30-40 minutes, then dropwise add cysteamine hydrochloride solution, add 2-(N-morpholino)ethanesulfonic acid solution, adjust the solution pH to 5.5-6, stir for 4-5 hours, react at 4-5°C for 10-14 hours, dialyze to obtain a thiolated sheep collagen fiber solution, and freeze-dry to obtain thiolated sheep collagen fiber particles.
[0019] More optimally, the preparation method of the sheep collagen fiber is: take sheep collagen powder and dissolve it in acetic acid, dialyze to neutrality to obtain a sheep collagen solution, add phosphate buffer, mix evenly, centrifuge, then resuspend the precipitate in phosphate buffer, centrifuge, and dry to obtain sheep collagen fibers.
[0020] More optimally, the method for preparing the sheep collagen powder is: taking sheepskin, breaking it, washing it, degreasing it with n-butanol, centrifuging it, washing it with water, and then using an acetic acid solution containing pepsin to extract the collagen, adjusting the pH value to neutral, inactivating the enzyme, dialyzing it, and freeze-drying it to obtain the sheep collagen powder.
[0021] More optimally, the concentration of hydrogen peroxide is 5-5.5 mmol / L.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. When silk fibroin particles are combined with collagen, hyaluronic acid and other substances and used as fillers for various tissues, they can have the advantages of multiple materials. At this time, the polymer filler can play a supporting and filling role. As the degradation process progresses, the silk fibroin particles are gradually released, which can stimulate tissue regeneration again.
[0024] 2. The present invention simultaneously adds silk fibroin gel particles and concentrated silk fibroin solution, and the self-reinforced assembly of concentrated silk fibroin and silk fibroin gel improves the mechanical properties of silk fibroin protein particles.
[0025] 3. The present invention adds sheep collagen fiber and thiolated hyaluronic acid, which can prolong the degradation time and provide scaffold space for tissue regeneration. The present invention also uses N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 2-(N-morpholino)ethanesulfonic acid to thiolate the sheep collagen fiber, so that the sheep collagen fiber contains thiol groups, and the thiolated hyaluronic acid and silk protein freeze-dried particles also have thiol groups. The three have good compatibility and better prolong the degradation time. At the same time, the present invention also uses hydrogen peroxide to cross-link it. By controlling the concentration of hydrogen peroxide to 5-5.5mmol / L, the stability of the material is increased, and its biodegradation rate is reduced, thereby further prolonging the degradation time. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] There is no specific restriction on the sources and models of the substances involved in the present invention, and illustratively include: thiolated hyaluronic acid: model: SH-HA-372, which can be purchased from Feifan Standard Technical Service Co., Ltd.; 6A raw silk, sourced from Hai'an Suhao Silk Co., Ltd., which is obtained by degumming raw silk by our company; pepsin: model: S10027, which can be purchased from Shanghai Yuanye Biotechnology Co., Ltd.; sodium hyaluronate gel: model: 20200701, which can be purchased from Shandong Baolijia Biotechnology Co., Ltd.
[0028] Example 1: A method for preparing a polymer filler containing silk fibroin particles, comprising the following steps:
[0029] Step 1: Preparation of lyophilized silk fibroin particles:
[0030] Take the degummed silk and dissolve it with 9.3 mol / L lithium bromide solution at 60°C, the bath ratio of the degummed silk to the lithium bromide is 1:5, and obtain dissolved silk fibroin;
[0031] The dissolved silk fibroin was cooled, placed in a dialysis bag with a molecular weight cut-off of 14 kDa, and dialyzed with purified water for three days before being taken out to obtain a silk fibroin solution;
[0032] The silk fibroin solution was filtered and centrifuged at 4°C and 9000 rpm for 25 minutes to obtain a silk fibroin solution with a concentration of 5 wt%; the silk fibroin solution was concentrated at 62°C to 17 wt%; water for injection was added to the concentrated silk fibroin solution to dilute it to 4 wt% to obtain a diluted silk fibroin solution;
[0033] The diluted silk solution was placed at 60°C again until a silk gel was formed;
[0034] The silk fibroin gel was granulated through a sieve, and the concentrated silk fibroin solution was added to the granulated silk fibroin gel particles, with the mass ratio of the granulated silk fibroin gel particles to the concentrated silk fibroin solution being 1:1; the mixture was evenly mixed, frozen at -60°C for 36 hours, freeze-dried, placed at room temperature for 2 days to absorb moisture, and crushed to obtain freeze-dried silk fibroin protein particles;
[0035] Step 2: Preparation of polymer filler containing silk fibroin particles:
[0036] 18 g of lyophilized silk fibroin particles, 5 g of thiolated hyaluronic acid, and 1000 mL of deionized water were mixed evenly, the pH value of the system was adjusted to 8 with 1 mol / L sodium hydroxide solution, mixed evenly at 1°C, 5 mmol / L hydrogen peroxide was added, reacted at 38°C for 25 min, dialyzed, and freeze-dried to obtain particles A; 16 parts of particles A and sodium hyaluronate gel were taken and mixed evenly to obtain a polymer filler containing silk fibroin particles.
[0037] Example 2: A method for preparing a polymer filler containing silk fibroin particles, comprising the following steps:
[0038] Step 1: Preparation of lyophilized silk fibroin particles:
[0039] Take the degummed silk and dissolve it with 9.3 mol / L lithium bromide solution at 60°C, the bath ratio of the degummed silk to the lithium bromide is 1:5, and obtain dissolved silk fibroin;
[0040] The dissolved silk fibroin was cooled, placed in a dialysis bag with a molecular weight cut-off of 14 kDa, and dialyzed with purified water for three days before being taken out to obtain a silk fibroin solution;
[0041] The silk fibroin solution was filtered and centrifuged at 4°C and 9000 rpm for 25 minutes to obtain a silk fibroin solution with a concentration of 5 wt%; the silk fibroin solution was concentrated at 62°C to 17 wt%; water for injection was added to the concentrated silk fibroin solution to dilute it to 4 wt% to obtain a diluted silk fibroin solution;
[0042] The diluted silk solution was placed at 60°C again until a silk gel was formed;
[0043] The silk fibroin gel was granulated through a sieve, and the concentrated silk fibroin solution was added to the granulated silk fibroin gel particles, with the mass ratio of the granulated silk fibroin gel particles to the concentrated silk fibroin solution being 1:1; the mixture was evenly mixed, frozen at -60°C for 36 hours, freeze-dried, placed at room temperature for 2 days to absorb moisture, and crushed to obtain freeze-dried silk fibroin protein particles;
[0044] Step 2: Preparation of sheep collagen fibers:
[0045] The sheepskin is taken, crushed, washed, degreased with 10% n-butanol, centrifuged, washed with water, and then collagen is extracted with a 0.5M acetic acid solution containing 1g / L pepsin, the pH value is adjusted to neutral, the enzyme is inactivated, dialyzed, and freeze-dried to obtain sheep collagen powder;
[0046] Preparation of sheep collagen fibers:
[0047] Take sheep collagen powder and dissolve it in 0.5M acetic acid, dialyze it to neutrality to obtain 3.5mg / mL sheep collagen solution, add 20mM phosphate buffer, mix well, centrifuge, and then resuspend the precipitate in phosphate buffer to a concentration of 3mg / mL, centrifuge, and dry to obtain sheep collagen fiber;
[0048] Step 3: Preparation of thiolated sheep collagen fibers:
[0049] 3 g of sheep collagen fiber and 50 mL of 0.5 M acetic acid were mixed evenly to obtain a sheep collagen fiber solution, cooled to 2°C, 0.2 g of N-hydroxysuccinimide and 0.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added, mixed evenly, reacted for 35 min, and then 50 mg / mL of cysteamine hydrochloride solution was added dropwise to make the cysteamine hydrochloride concentration of the final solution 55 mmol / L, 2-(N-morpholino)ethanesulfonic acid solution was added, the pH value of the solution was adjusted to 5.5, stirred for 4.5 h, reacted at 4°C for 12 h, dialyzed to obtain a thiolated sheep collagen fiber solution, and freeze-dried to obtain thiolated sheep collagen fiber particles;
[0050] Step 4: Preparation of polymer filler containing silk fibroin particles:
[0051] 18 g of lyophilized silk fibroin particles, 5 g of thiolated hyaluronic acid, and 1000 mL of deionized water were mixed evenly, the pH value of the system was adjusted to 8 with 1 mol / L sodium hydroxide solution, 3 g of thiolated sheep collagen fiber particles were added, and the mixture was mixed evenly at 1°C, 5 mmol / L hydrogen peroxide was added, and the mixture was reacted at 38°C for 25 min, dialyzed, and freeze-dried to obtain particles A; 16 portions of particles A and sodium hyaluronate gel were taken and mixed evenly to obtain a polymer filler containing silk fibroin particles.
[0052] Example 3: A method for preparing a polymer filler containing silk fibroin particles, comprising the following steps:
[0053] Step 1: Preparation of lyophilized silk fibroin particles:
[0054] Take the degummed silk and dissolve it with 9.3 mol / L lithium bromide solution at 60°C, the bath ratio of the degummed silk to lithium bromide is 1:4, and obtain dissolved silk fibroin;
[0055] The dissolved silk fibroin was cooled, placed in a dialysis bag with a molecular weight cut-off of 14 kDa, and dialyzed with purified water for three days before being taken out to obtain a silk fibroin solution;
[0056] The silk fibroin solution was filtered and centrifuged at 5°C and 9000 rpm for 20 minutes to obtain a silk fibroin solution with a concentration of 3 wt%; the silk fibroin solution was concentrated at 60°C to 15 wt%; water for injection was added to the concentrated silk fibroin solution to dilute it to 2 wt% to obtain a diluted silk fibroin solution;
[0057] The diluted silk solution was placed at 60°C again until a silk gel was formed;
[0058] The silk fibroin gel was granulated through a screen, and the concentrated silk fibroin solution was added to the granulated silk fibroin gel particles, with the mass ratio of the granulated silk fibroin gel particles to the silk fibroin in the concentrated silk fibroin solution being 1:0.5; the mixture was evenly mixed, frozen at -40°C for 24 hours, freeze-dried, placed at room temperature for 1 day to absorb moisture, and crushed to obtain freeze-dried silk fibroin protein particles;
[0059] Step 2: Preparation of sheep collagen fibers:
[0060] The sheepskin is taken, crushed, washed, degreased with 10% n-butanol, centrifuged, washed with water, and then collagen is extracted with a 0.5M acetic acid solution containing 1g / L pepsin, the pH value is adjusted to neutral, the enzyme is inactivated, dialyzed, and freeze-dried to obtain sheep collagen powder;
[0061] Take sheep collagen powder and dissolve it in 0.5M acetic acid, dialyze it to neutrality to obtain 3.5mg / mL sheep collagen solution, add 20mM phosphate buffer, mix well, centrifuge, and then resuspend the precipitate in phosphate buffer to a concentration of 3mg / mL, centrifuge, and dry to obtain sheep collagen fiber;
[0062] Step 3: Preparation of thiolated sheep collagen fibers:
[0063] 3 g of sheep collagen fiber and 50 mL of 0.5 M acetic acid were mixed evenly to obtain a sheep collagen fiber solution, cooled to 2°C, 0.2 g of N-hydroxysuccinimide and 0.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added, mixed evenly, reacted for 30 min, and then 50 mg / mL of cysteamine hydrochloride solution was added dropwise to make the cysteamine hydrochloride concentration of the final solution 55 mmol / L, 2-(N-morpholino)ethanesulfonic acid solution was added, the pH value of the solution was adjusted to 5.5, stirred for 4 h, reacted at 4°C for 10 h, dialyzed to obtain a thiolated sheep collagen fiber solution, and freeze-dried to obtain thiolated sheep collagen fiber particles;
[0064] Step 4: Preparation of polymer filler containing silk fibroin particles:
[0065] 18 g of lyophilized silk fibroin particles, 5 g of thiolated hyaluronic acid, and 1000 mL of deionized water were mixed evenly, the pH value of the system was adjusted to 8 with 1 mol / L sodium hydroxide solution, 3 g of thiolated sheep collagen fiber particles were added, and the mixture was mixed evenly at 0°C, 5 mmol / L hydrogen peroxide was added, and the mixture was reacted at 35°C for 20 min, dialyzed, and freeze-dried to obtain particles A; 16 portions of particles A and sodium hyaluronate gel were taken and mixed evenly to obtain a polymer filler containing silk fibroin particles.
[0066] Example 4: A method for preparing a polymer filler containing silk fibroin particles, comprising the following steps:
[0067] Step 1: Preparation of lyophilized silk fibroin particles:
[0068] Take the degummed silk and dissolve it with 9.3 mol / L lithium bromide solution at 60°C, the bath ratio of the degummed silk to the lithium bromide is 1:10, and obtain dissolved silk fibroin;
[0069] The dissolved silk fibroin was cooled, placed in a dialysis bag with a molecular weight cut-off of 14 kDa, and dialyzed with purified water for three days before being taken out to obtain a silk fibroin solution;
[0070] The silk fibroin solution was filtered and centrifuged at 5°C and 9000 rpm for 30 minutes to obtain a silk fibroin solution with a concentration of 6 wt%; the silk fibroin solution was concentrated at 65°C to 20 wt%; water for injection was added to the concentrated silk fibroin solution to dilute it to 6 wt% to obtain a diluted silk fibroin solution;
[0071] The diluted silk solution was placed at 60°C again until a silk gel was formed;
[0072] The silk fibroin gel was granulated through a sieve, and the concentrated silk fibroin solution was added to the granulated silk fibroin gel particles, and the mass ratio of the granulated silk fibroin gel particles to the concentrated silk fibroin solution was 1:2; the mixture was evenly mixed, frozen at -80°C for 48 hours, freeze-dried, placed at room temperature for 3 days to absorb moisture, and crushed to obtain freeze-dried silk fibroin protein particles;
[0073] Step 2: Preparation of sheep collagen fibers:
[0074] The sheepskin is taken, crushed, washed, degreased with 10% n-butanol, centrifuged, washed with water, and then collagen is extracted with a 0.5M acetic acid solution containing 1g / L pepsin, the pH value is adjusted to neutral, the enzyme is inactivated, dialyzed, and freeze-dried to obtain sheep collagen powder;
[0075] Preparation of sheep collagen fibers:
[0076] Take sheep collagen powder and dissolve it in 0.5M acetic acid, dialyze it to neutrality to obtain 3.5mg / mL sheep collagen solution, add 20mM phosphate buffer, mix well, centrifuge, and then resuspend the precipitate in phosphate buffer to a concentration of 3mg / mL, centrifuge, and dry to obtain sheep collagen fiber;
[0077] Step 3: Preparation of thiolated sheep collagen fibers:
[0078] 3 g of sheep collagen fiber and 50 mL of 0.5 M acetic acid were mixed evenly to obtain a sheep collagen fiber solution, cooled to 3°C, 0.2 g of N-hydroxysuccinimide and 0.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added, mixed evenly, reacted for 40 min, and then 50 mg / mL of cysteamine hydrochloride solution was added dropwise to make the cysteamine hydrochloride concentration of the final solution 55 mmol / L, 2-(N-morpholino)ethanesulfonic acid solution was added, the pH value of the solution was adjusted to 6, stirred for 5 h, reacted at 5°C for 14 h, dialyzed to obtain a thiolated sheep collagen fiber solution, and freeze-dried to obtain thiolated sheep collagen fiber particles;
[0079] Step 4: Preparation of polymer filler containing silk fibroin particles:
[0080] 18 g of lyophilized silk fibroin particles, 5 g of thiolated hyaluronic acid, and 1000 mL of deionized water were mixed evenly, the pH value of the system was adjusted to 8 with 1 mol / L sodium hydroxide solution, 3 g of thiolated sheep collagen fiber particles were added, and the mixture was mixed evenly at 2°C, 5 mmol / L hydrogen peroxide was added, and the mixture was reacted at 40°C for 30 min, dialyzed, and freeze-dried to obtain particles A; 16 portions of particles A and sodium hyaluronate gel were taken and mixed evenly to obtain a polymer filler containing silk fibroin particles.
[0081] Comparative Example 1: The sheep collagen fiber is not subjected to thiol modification, and the rest is the same as Example 2:
[0082] Step 1: Preparation of lyophilized silk fibroin particles:
[0083] Take the degummed silk and dissolve it with 9.3 mol / L lithium bromide solution at 60°C, the bath ratio of the degummed silk to the lithium bromide is 1:5, and obtain dissolved silk fibroin;
[0084] The dissolved silk fibroin was cooled, placed in a dialysis bag with a molecular weight cut-off of 14 kDa, and dialyzed with purified water for three days before being taken out to obtain a silk fibroin solution;
[0085] The silk fibroin solution was filtered and centrifuged at 4°C and 9000 rpm for 25 minutes to obtain a silk fibroin solution with a concentration of 5 wt%; the silk fibroin solution was concentrated at 62°C to 17 wt%; water for injection was added to the concentrated silk fibroin solution to dilute it to 4 wt% to obtain a diluted silk fibroin solution;
[0086] The diluted silk solution was placed at 60°C again until a silk gel was formed;
[0087] The silk fibroin gel was granulated through a sieve, and the concentrated silk fibroin solution was added to the granulated silk fibroin gel particles, with the mass ratio of the granulated silk fibroin gel particles to the concentrated silk fibroin solution being 1:1; the mixture was evenly mixed, frozen at -60°C for 36 hours, freeze-dried, placed at room temperature for 2 days to absorb moisture, and crushed to obtain freeze-dried silk fibroin protein particles;
[0088] Step 2: Preparation of sheep collagen fibers:
[0089] The sheepskin is taken, crushed, washed, degreased with 10% n-butanol, centrifuged, washed with water, and then collagen is extracted with a 0.5M acetic acid solution containing 1g / L pepsin, the pH value is adjusted to neutral, the enzyme is inactivated, dialyzed, and freeze-dried to obtain sheep collagen powder;
[0090] Take sheep collagen powder and dissolve it in 0.5M acetic acid, dialyze it to neutrality to obtain 3.5mg / mL sheep collagen solution, add 20mM phosphate buffer, mix well, centrifuge, and then resuspend the precipitate in phosphate buffer to a concentration of 3mg / mL, centrifuge, and dry to obtain sheep collagen fiber;
[0091] Step 3: Preparation of sheep collagen fiber particles:
[0092] 3 g of sheep collagen fiber and 50 mL of 0.5 M acetic acid were mixed evenly to obtain a sheep collagen fiber solution, and then freeze-dried to obtain sheep collagen fiber particles;
[0093] Step 4: Preparation of polymer filler containing silk fibroin particles:
[0094] 18 g of lyophilized silk fibroin particles, 5 g of thiolated hyaluronic acid, and 1000 mL of deionized water were mixed evenly, the pH value of the system was adjusted to 8 with 1 mol / L sodium hydroxide solution, 3 g of sheep collagen fiber particles were added, and the mixture was mixed evenly at 1°C, 5 mmol / L of hydrogen peroxide was added, and the mixture was reacted at 38°C for 25 min, dialyzed, and freeze-dried to obtain particles A; 16 portions of particles A and sodium hyaluronate gel were taken and mixed evenly to obtain a polymer filler containing silk fibroin particles.
[0095] Comparative Example 2: No thiolated hyaluronic acid was added, and the rest was the same as Example 2:
[0096] Step 1: Preparation of lyophilized silk fibroin particles:
[0097] Take the degummed silk and dissolve it with 9.3 mol / L lithium bromide solution at 60°C, the bath ratio of the degummed silk to the lithium bromide is 1:5, and obtain dissolved silk fibroin;
[0098] The dissolved silk fibroin was cooled, placed in a dialysis bag with a molecular weight cut-off of 14 kDa, and dialyzed with purified water for three days before being taken out to obtain a silk fibroin solution;
[0099] The silk fibroin solution was filtered and centrifuged at 4°C and 9000 rpm for 25 minutes to obtain a silk fibroin solution with a concentration of 5 wt%; the silk fibroin solution was concentrated at 62°C to 17 wt%; water for injection was added to the concentrated silk fibroin solution to dilute it to 4 wt% to obtain a diluted silk fibroin solution;
[0100] The diluted silk solution was placed at 60°C again until a silk gel was formed;
[0101] The silk fibroin gel was granulated through a sieve, and the concentrated silk fibroin solution was added to the granulated silk fibroin gel particles, with the mass ratio of the granulated silk fibroin gel particles to the concentrated silk fibroin solution being 1:1; the mixture was evenly mixed, frozen at -60°C for 36 hours, freeze-dried, placed at room temperature for 2 days to absorb moisture, and crushed to obtain freeze-dried silk fibroin protein particles;
[0102] Step 2: Preparation of sheep collagen fibers:
[0103] The sheepskin is taken, crushed, washed, degreased with 10% n-butanol, centrifuged, washed with water, and then collagen is extracted with a 0.5M acetic acid solution containing 1g / L pepsin, the pH value is adjusted to neutral, the enzyme is inactivated, dialyzed, and freeze-dried to obtain sheep collagen powder;
[0104] Preparation of sheep collagen fibers:
[0105] Take sheep collagen powder and dissolve it in 0.5M acetic acid, dialyze it to neutrality to obtain 3.5mg / mL sheep collagen solution, add 20mM phosphate buffer, mix well, centrifuge, and then resuspend the precipitate in phosphate buffer to a concentration of 3mg / mL, centrifuge, and dry to obtain sheep collagen fiber;
[0106] Step 3: Preparation of thiolated sheep collagen fibers:
[0107] 3 g of sheep collagen fiber and 50 mL of 0.5 M acetic acid were mixed evenly to obtain a sheep collagen fiber solution, cooled to 2°C, 0.2 g of N-hydroxysuccinimide and 0.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride were added, mixed evenly, reacted for 35 min, and then 50 mg / mL of cysteamine hydrochloride solution was added dropwise to make the cysteamine hydrochloride concentration of the final solution 55 mmol / L, 2-(N-morpholino)ethanesulfonic acid solution was added, the pH value of the solution was adjusted to 5.5, stirred for 4.5 h, reacted at 4°C for 12 h, dialyzed to obtain a thiolated sheep collagen fiber solution, and freeze-dried to obtain thiolated sheep collagen fiber particles;
[0108] Step 4: Preparation of polymer filler containing silk fibroin particles:
[0109] 18 g of lyophilized silk fibroin particles and 1000 mL of deionized water were mixed evenly, the pH value of the system was adjusted to 8 with 1 mol / L sodium hydroxide solution, 3 g of thiolated sheep collagen fiber particles were added, and the mixture was mixed evenly at 1°C, 5 mmol / L hydrogen peroxide was added, and the mixture was reacted at 38°C for 25 min, dialyzed, and freeze-dried to obtain particles A; 16 portions of particles A and sodium hyaluronate gel were taken and mixed evenly to obtain a polymer filler containing silk fibroin particles.
[0110] Comparative Example 3: In step 4, the concentration of hydrogen peroxide is 3 mmol / L, and the rest is the same as in Example 2.
[0111] experiment:
[0112] Experiment 1: In vitro degradation performance test: Take the polymer filler containing silk fibroin particles obtained in Examples 1-4 and Comparative Examples 1-3, weigh it, record the initial weight as m0, transfer it and immerse it in a phosphate buffer containing 20U / mL collagenase, and place it in an air bath shaker at a temperature of 37°C and a shaking speed of 150rpm for the experiment; take out the sample at regular intervals, freeze-dry it, weigh it as m1, and replace it with a new degradation solution until the condition (m0-m1) / m0>0.99 is met, it is considered to be completely degraded, and its complete degradation time is recorded.
[0113] Experiment 2: Injectability test: The polymer fillers containing silk fibroin particles obtained in Examples 1-4 and Comparative Examples 1-3 were loaded into a 1 mL syringe and equipped with a 27G injection needle to simulate actual use. The push rod was pushed at a constant pushing speed of 30 mm / min, and the pushing displacement was 20 mm. The sample in the syringe was pushed out through the needle. Within a certain compression displacement, the compression load of the injectable gel varied between 8 and 16 N.
[0114] Degradation time / d Average pushing force / N Example 1 217 10.4 Example 2 267 13.7 Example 3 264 13.5 Example 4 268 13.8 Comparative Example 1 244 13.2 Comparative Example 2 235 12.1 Comparative Example 3 252 11.4
[0115] Conclusion: From the data comparison in the table, it can be seen that compared with Example 1, the average pushing force of Examples 2-4 and Comparative Examples 1-3 has increased slightly, but the pushing force is between 8 and 16N, which is still suitable for injection. Comparative Example 1 does not perform thiol modification on the sheep collagen fiber, and the cross-linking and compatibility decrease, and the degradation time decreases. Comparative Example 2 does not add thiol hyaluronic acid, and the anti-degradation performance decreases. The concentration of hydrogen peroxide in Comparative Example 3 is 3mmo l / L. At this time, the concentration of hydrogen peroxide becomes lower, the stability of the material decreases, the biodegradation rate increases, and the degradation time becomes shorter. Examples 2-4 of the present application, sheep collagen fiber and thiol hyaluronic acid are added, which can prolong the degradation time and provide a scaffold space for tissue regeneration. The sheep collagen fiber is thiol-modified so that the sheep collagen fiber contains a thiol group, and there is also a thiol group on the thiol hyaluronic acid and silk protein freeze-dried particles. The three have good compatibility and better prolong the degradation time. The invention increases the stability of the material and reduces its biodegradation rate by controlling the concentration of hydrogen peroxide to 5-5.5 mmol / L, thereby further prolonging the degradation time.
[0116] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a polymer filler containing silk fibroin particles, characterized in that: The following steps are involved: Step 1: taking the degummed silk, dissolving it with a lithium bromide solution to obtain dissolved silk fibroin; cooling, dialyzing, and taking out the dissolved silk fibroin to obtain a silk fibroin solution; Step 2: taking the silk fibroin solution, filtering, centrifuging, concentrating at 60-65° C., and adding injection water to dilute to obtain a diluted silk fibroin solution; Step 3: placing the diluted silk solution at 60-65°C until a silk gel is formed; Step 4: Take the silk fibroin gel, granulate it, add the concentrated silk fibroin solution to the granulated silk fibroin gel particles, mix them evenly, freeze them at -40°C to -80°C for 24-48h, freeze-dry them, place them at 25-30°C to absorb moisture for 1-3d, and crush them to obtain freeze-dried silk fibroin particles; Step 5: Mix the lyophilized silk fibroin particles, thiolated hyaluronic acid, and deionized water evenly, use sodium hydroxide solution to adjust the pH value of the system to 8-8.5, add thiolated sheep collagen fiber particles, mix evenly at 0-2°C, add hydrogen peroxide, react at 35-40°C for 20-30 minutes, dialyze, and freeze-dry to obtain particles A; take particles A and sodium hyaluronate gel, mix evenly to obtain a polymer filler containing silk fibroin particles.
2. The method for preparing a polymer filler containing silk fibroin particles according to claim 1, characterized in that: In step 1, the bath ratio of the degummed silk to lithium bromide is 1:(4-10).
3. The method for preparing a polymer filler containing silk fibroin particles according to claim 1, characterized in that: In step 2, the concentration of the diluted silk fibroin solution is 2wt%-6wt%.
4. The method for preparing a polymer filler containing silk fibroin particles according to claim 1, characterized in that: In step 4, the mass ratio of the granulated silk fibroin gel particles to the silk fibroin in the concentrated silk fibroin solution is 1:(0.2-2).
5. The method for preparing a polymer filler containing silk fibroin particles according to claim 1, characterized in that: In step 2, the centrifugation condition is: centrifugation at 9000 rpm for 20-30 min.
6. The method for preparing a polymer filler containing silk fibroin particles according to claim 1, characterized in that: The preparation method of the thiolated sheep collagen fiber particles is as follows: sheep collagen fibers and acetic acid are mixed evenly to obtain a sheep collagen fiber solution, the temperature is lowered to 2-3°C, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added, the mixture is mixed evenly, the mixture is reacted for 30-40 minutes, a cysteamine hydrochloride solution is added dropwise, a 2-(N-morpholino)ethanesulfonic acid solution is added, the pH value of the solution is adjusted to 5.5-6, the mixture is stirred for 4-5 hours, the mixture is reacted at 4-5°C for 10-14 hours, the solution is dialyzed, a thiolated sheep collagen fiber solution is obtained, and the solution is freeze-dried to obtain thiolated sheep collagen fiber particles.
7. The method for preparing a polymer filler containing silk fibroin particles according to claim 6, characterized in that: The preparation method of the sheep collagen fiber is as follows: dissolving sheep collagen powder in acetic acid, dialyzing to neutrality to obtain a sheep collagen solution, adding a phosphate buffer, mixing evenly, centrifuging, and then resuspending the precipitate in a phosphate buffer, centrifuging, and drying to obtain the sheep collagen fiber.
8. The method for preparing a polymer filler containing silk fibroin particles according to claim 7, characterized in that: The preparation method of the sheep collagen powder comprises the following steps: taking sheepskin, breaking it, washing it, performing a degreasing treatment with n-butanol, centrifuging it, washing it with water, then extracting collagen with an acetic acid solution containing pepsin, adjusting the pH value to neutral, inactivating the enzyme, dialyzing it, and freeze-drying it to obtain the sheep collagen powder.
9. The method for preparing a polymer filler containing silk fibroin particles according to claim 1, characterized in that: The concentration of the hydrogen peroxide is 5-5.5 mmol / L.
Citation Information
Patent Citations
Silk fibroin-sodium hyaluronate cross-linked dual-network gel and preparation method thereof
CN111440340A
Photo-crosslinked silk fibroin / hyaluronic acid hydrogel barrier material as well as preparation method and application thereof
CN116217943A
Silk Fibroin Hydrogels and Uses Thereof
US20110008406A1
Ultra-thin film silk fibroin / collagen composite implant and manufacturing method therefor
US20170266345A1
Cited By
Absorbable zigzag material and preparation method thereof
CN121338074A
Polylactic acid skin filler and preparation method thereof
CN121338096A